The risk of salmonellae shedding by dogs fed Salmonella-contaminated commercial raw food diets - Finley, Rita (Canadian Veterinary Medical Association, 2007)
Twenty-eight research dogs were enrolled to determine the prevalence of salmonellae shedding after consumption of 1 Salmonella-contaminated commercial raw food diet meal. Sixteen dogs were exposed to Salmonella-contaminated commercial raw food diets and 12 to Salmonella-free commercial raw food diets. Seven of the exposed dogs shed salmonellae 1–7 days after consumption of Salmonella-contaminated raw food diets. None of the dogs fed Salmonella-free diets shed salmonellae. No clinical signs were observed in either group. Five of the 7 dogs shed the same serotypes as those recovered from food samples used for feeding. Results showed the same serotypes and antimicrobial resistance pattern in 2 of the 7 shedders. Dogs fed Salmonella-contaminated raw food diets can shed salmonellae and may, therefore, be a source of environmental contamination potentially leading to human or animal illness.